INDONESIAN MARKETING STUDENTS’ FEAR OF PUBLIC SPEAKING USING ENGLISH LANGUAGE - Rizki Muhammad Ardian Setiadi; Simanjuntak, Daniel (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
Students are expected to be proficient in conducting public speaking using English language. However, many students struggle to speak in front of many people because of the fear that they experience. The present study aimed to examine the fears students experience when speaking in public. This study employed descriptive qualitative study. Qualitative survey was distributed to the students to collect the data. The survey consisted of four questions regarding fear of public speaking. As many as 50 marketing students who had taken public speaking course were asked to fill in the survey. The data collected was examine through qualitative thematic analysis. The results showed four themes extracted from the survey, including nervousness, fears, practice and facilitating practice.